2022
DOI: 10.15298/arctoa.31.14
|View full text |Cite
|
Sign up to set email alerts
|

New data on the genus Oxyrrhynchium (Brachytheciaceae, Bryophyta) in The Russian Far East

Abstract: The genus Oxyrrhynchium was known in the Russian Far East as represented by a single species, O. savatieri, revealed recently in the Kuril Islands. The finding of O. vagans, a much more southern species, in Primorsky Territory was unexpected. When sporophytes are present, this species is easily differentiated from most other species of the genus by smooth, not rough setae. However, specimens with sporophytes are rare in Oxyrrhynchium and without sporophytes their identification often cannot be certain. Thus we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…si.edu/botany/codes-proposals/display_new.cfm; checked 7 March 2023). The well-known, apparently European-North American (Ignatov et al 2022), O. hians and its close relatives are pretty similar to each other in appearance, with at least some phenotypes having sparsely inserted stem leaves, complanate or sub-complanate ovate or oblong-ovate branch leaves, often with a strong costa, and, except in O. vagans (A.Jaeger) Ignatov & Huttunen, a rough seta. Ignatov and Huttunen (2002), Huttunen and Ignatov (2004) and Wynns et al (2009) all observed that several morphologically deviating aquatic species form a clade sister to the species around O. hians, and Wynns et al (2009) made some of the formal combinations for such species within Oxyrrhynchium.…”
Section: Oxyrrhynchium Hians (Brachytheciaceae Bryophyta) Includes Se...mentioning
confidence: 93%
See 1 more Smart Citation
“…si.edu/botany/codes-proposals/display_new.cfm; checked 7 March 2023). The well-known, apparently European-North American (Ignatov et al 2022), O. hians and its close relatives are pretty similar to each other in appearance, with at least some phenotypes having sparsely inserted stem leaves, complanate or sub-complanate ovate or oblong-ovate branch leaves, often with a strong costa, and, except in O. vagans (A.Jaeger) Ignatov & Huttunen, a rough seta. Ignatov and Huttunen (2002), Huttunen and Ignatov (2004) and Wynns et al (2009) all observed that several morphologically deviating aquatic species form a clade sister to the species around O. hians, and Wynns et al (2009) made some of the formal combinations for such species within Oxyrrhynchium.…”
Section: Oxyrrhynchium Hians (Brachytheciaceae Bryophyta) Includes Se...mentioning
confidence: 93%
“…Oxyrrhynchium hians, as currently understood in Europe, is highly variable morphologically and both subspecific and closely related species-level taxa have often been recognized (Limpricht 1895-1904, Brotherus 1923, Dixon 1924, Nyholm 1965. Further, based on nuclear ITS, Ignatov et al (2022) found two subgroups of O. hians. Considering the wide range of habitats inhabited and the wide morphologic variation in European O. hians, this suggests that it is worth exploring the species in more detail.…”
Section: Oxyrrhynchium Hians (Brachytheciaceae Bryophyta) Includes Se...mentioning
confidence: 97%
“…Austin ex C.F. Parker, which are widespread and common in the area (results of this ongoing revision are partly disclosed in Ignatov et al, 2022). The same is true for East Asian Orthotrichaceae, which remain scarcely explored with the integrative taxonomic approach.…”
Section: B C Amentioning
confidence: 96%